The Controversy over the Use of 14-Karat Gold Nisab in Determining Professional Zakat: A Fiqh Review and Its Impact on Zakat Justice - Imam Agung Prakoso (Jurnal El-Thawalib, 2026)
This study examines the controversy surrounding the use of 14-karat gold in determining the nisab for professional zakat from the perspective of Islamic jurisprudence (fiqh) and distributive justice. However, the policy implemented by the National Zakat Agency (BAZNAS) using 14-karat gold has sparked debate due to its potential to lower the real value of the nisab. This study employed library research with a qualitative approach. Primary data came from the Qur'an, hadith, and policy documents related to the nisab for professional zakat, while secondary data were obtained from relevant fiqh books, books, and scientific journal articles. The results indicate that the use of 14-karat gold, although facilitating the implementation of zakat, has the potential to expand the obligation of zakat to groups who are not yet fully economically capable. From the perspective of maqashid sharia, this could disrupt the principles of justice (al 'adl) and balance (tawazun). Therefore, a more integrative reconstruction of the nisab standard is needed to align with the principles of Islamic jurisprudence and the goals of social justice in zakat.